The effects of chronic trans-resveratrol supplementation on aspects of cognitive function, mood, sleep, health and cerebral blood flow in healthy, young humans. Issue 9 (7th September 2015) - Wightman, Emma L.; Haskell-Ramsay, Crystal F.; Reay, Jonathon L.; Williamson, Gary; Dew, Tristan; Zhang, Wei; Kennedy, David O.
Abstract: Single doses of resveratrol have previously been shown to increase cerebral blood flow (CBF) with no clear effect on cognitive function or mood in healthy adults. Chronic resveratrol consumption may increase the poor bioavailability of resveratrol or otherwise potentiate its psychological effects. In this randomised, double-blind, placebo-controlled, parallel-groups study, a total of sixty adults aged between 18 and 30 years received either placebo or resveratrol for 28 d. On the 1st and 28th day of treatment, the performance of cognitively demanding tasks (serial subtractions, rapid visual information processing and 3-Back) ( n 41 complete data sets) was assessed, alongside blood pressure ( n 26) and acute (near-IR spectroscopy (NIRS)) and chronic (transcranial Doppler) measures of CBF ( n 46). Subjective mood, sleep quality and health questionnaires were completed at weekly intervals ( n 53/54). The results showed that the cognitive effects of resveratrol on day 1 were restricted to more accurate but slower serial subtraction task performance. The only cognitive finding on day 28 was a beneficial effect of resveratrol on the accuracy of the 3-Back task before treatment consumption. Subjective ratings of 'fatigue' were significantly lower across the entire 28 d in the resveratrol condition. Resveratrol also resulted in modulation of CBF parameters on day 1, as assessed by NIRS, and significantly increased diastolic blood pressure on day 28. Levels of resveratrol metabolites were significantly higher both before and after the day's treatment on day 28, in comparison with day 1. These results confirm the acute CBF effects of resveratrol and the lack of interpretable cognitive effects.